1. Efectuează
a) √3(√2a-√3b) =
b) 2√2x(3√2-4x) =
c) √6y(√3y+2) =
d) 2√6( 3√2x - 2√3) =
e) 1,5(8 - 7x) - 2,3 ( x - 1 )
mă ajută cineva ? :o3
Răspunsuri la întrebare
Răspuns de
6
a) √3(√2a-√3b) = √6a-3√b
b) 2√2x(3√2-4x) =12-8√2x=4(3-2√2x)
c) √6y(√3y+2) = 3y√2+2√6y
d) 2√6( 3√2x - 2√3) =12√3-12√2=12(√3-√2)
e) 1,5(8 - 7x) - 2,3 ( x - 1 )=12-10,5x-2,3x+2,3=14,3-12,8x
b) 2√2x(3√2-4x) =12-8√2x=4(3-2√2x)
c) √6y(√3y+2) = 3y√2+2√6y
d) 2√6( 3√2x - 2√3) =12√3-12√2=12(√3-√2)
e) 1,5(8 - 7x) - 2,3 ( x - 1 )=12-10,5x-2,3x+2,3=14,3-12,8x
Alte întrebări interesante
Franceza,
9 ani în urmă
Limba română,
9 ani în urmă
Biologie,
9 ani în urmă
Arte,
10 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă